Pengaruh Obesitas pada Status Imunitas Individu Terhadap Infeksi Virus Dan Bakteri - ERNY; OKKY PRASETYO; AYLI SOEKANTO; ASTRID AMANDA (Universitas Hang Tuah, 2021)
Obesity is a chronic disorder which the incidence rate increases rapidly, especially in the Covid-19 pandemic due to limited daily physical activity and efforts to increase daily intake even though the initial goal is to increase immunity. Whatever the reason, obesity, is the part of malnutrition that must be watched out because it actually has big impact on health problems that can be fatal. What is highlighted here is the disruption of the immune system against bacterial or viral infections. With the advancement of medical science in the field of biomolecules, many parameters of the immune system have been shown to decrease both in quality and quantity in obesity conditions that cause susceptibility to infection. Keywords : obesity, immunity system, bacterial and viral infection